A postmodern accounting theory : an institutional approach - Breton, G. (Emerald Publishing Limited, 2018)
Drawing upon frameworks employed in the human sciences, Breton builds a multi-faceted theory of accounting, conceiving it as a fundamentally social activity that puts preparers of financial statements in contact with users in order to help them make economic decisions, and analyzing the behavior of preparers and users.
Keywords: Accounting.; Business & Economics -- Accounting -- General.; elektronické knihy; electronic books